Ultrasonic rangefinder for an obstacle detection system when moving a mobile robot - Bazykin, Sergey; Urvaev, Ilya (Известия высших учебных заведений. Поволжский регион:Технические науки, 2023)
Background. In recent years, robots have crossed the line of experimental and small-scale samples and have become actively used both as household systems and as complexes, on which, sometimes, our life and health depend. The object of the research is ultrasonic sensors for a mobile robot. Robot orientation methods in an environment characterized by a high level of dynamic uncertainty are the subject of the research. The purpose of the study is to increase the accuracy and reliability of determining the distance to the obstacle and adjusting the subsequent movement. Materials and methods. The study was carried out using schematic modeling in the Proteus software environment, as well as a full-scale experiment using an ultrasonic rangefinder. Results. The obtained results of field tests of the ultrasonic rangefinder of the robot are consistent with the results of circuit modeling. Conclusions. The results obtained showed the possibility of using ultrasonic rangefinders in systems for detecting obstacles.